Variation Trend of Flavor Components at Different Growth Stages of Chinese Chives Allium tuberosum (Journal of Agriculture and Veterinary Science, 2025)
Chinese chives are valued for their culinary and medicinal properties. Chinese chive possesses anti-inflammatory, antibacterial, antioxidant, illness prevention, and other health benefits, according to global studies. Studies analysed the complete plant for volatiles with varied food processing and therapeutic properties, but little is known about volatile levels at different plant growth stages. This study examined flavour component variation in Chinese chives at different development phases. The study found that total volatile chemicals of Fu Jiu Bao F1 increased initially and subsequently dropped, approaching peak at 30 DAT; whereas Jiu Xing 22 climbed gradually and approaching peak at fruiting. Fujibao F1 has 9, 18, and 15 volatiles in leaf sheath, leaf, and root. Thus, Fujibao F1 was suitable for harvesting vegetative organs, while Jiuxing 22 was suitable for harvesting chives stem, and its seeds and inflorescence had greater condiment potential. Overall volatile components of Chinese chive changed dynamically at different phases, although overall contents in different organs were consistent. In variety Jiu Xing 22, total volatile contents varied abnormally, while variety Fu Jiu Bao F1 had considerable constancy in volatile contents at all organ stages. Fu Jiu Bao F1 leaves had greater volatile content than roots and leaf sheath during vegetative development (seedling, 30 days after transplanting, and harvesting). However, Jiu Xing 22 root volatiles were greater than leaf sheath and leaves. During flowering, Fu Jiu Bao F1 mature flowers had the greatest volatile chemicals (530.6μg/g) while Jiu Xing 22 had the highest in the leaf sheath. At fruiting, Fu Jiu Bao F1 had more volatile concentration (252.16µg/g) in seeds than other organs, while Jiuxing 22 had higher volatiles in leaf sheath. The E-Nose examination discovered aromatic, broad range, sulphur organic, hydrogen, arom-aliph, broad methane, broad alcohol, and methane aliph, although plant growth stages may affect flavour, fragrance, and other features.